2012
DOI: 10.1021/ct300076y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Flap Dynamics in Wild-Type and a Drug Resistant Variant of HIV-1 Protease Revealed by Molecular Dynamics and NMR Relaxation

Abstract: In the rapidly evolving disease of HIV drug resistance readily emerges, nullifying the effectiveness of therapy. Drug resistance has been extensively studied in HIV-1 protease where resistance occurs when the balance between enzyme inhibition and substrate recognition and turn-over is perturbed to favor catalytic activity. Mutations which confer drug resistance can impact the dynamics and structure of both the bound and unbound forms of the enzyme. Flap+ is a multi-drug-resistant variant of HIV-1 protease with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(99 citation statements)
references
References 54 publications
3
96
0
Order By: Relevance
“…Fig. 8 shows plots of S 2 values determined for apo-inactive constructs Bi, PR5i, and AEi The results of Bi are similar to those obtained previously for a related subtype B construct called PMPR (19,21,31,59,64). Consistent with earlier findings, S 2 values plotted as a function of residue number (Fig.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Fig. 8 shows plots of S 2 values determined for apo-inactive constructs Bi, PR5i, and AEi The results of Bi are similar to those obtained previously for a related subtype B construct called PMPR (19,21,31,59,64). Consistent with earlier findings, S 2 values plotted as a function of residue number (Fig.…”
supporting
confidence: 81%
“…curling upon interaction with inhibitors (31). To gain insight regarding the origin of this additional curled flap conformation, a combination of four naturally occurring polymorphisms common in the sequences of subtypes A, F, and C were introduced into subtype B.…”
Section: Hiv-1 Protease (Hiv-1 Pr)mentioning
confidence: 99%
“…Although crystal structures provide key insights, alteration of dynamic behavior, not captured by static structures, is emerging as an additional contribution to mechanisms of drug resistance (37,38). We found that drug resistance mutations in the protease or in the native substrate disturbed the active site dynamics, which was restored in all coevolved complexes bearing complementary mutations in both the protease and the substrate.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, experimental studies have shown that there is a relationship between conformational sampling and drug resistance in HIV-PR (Cai et al, 2014;Cai et al 2012Foulkes-Murzycki et al, 2013Gibbs, 2014 andde Vera et al, 2013). Therefore, understanding functional dynamics of the flaps of HIV-PR is of great importance to the development of new HIV-PR inhibitors.…”
Section: Introductionmentioning
confidence: 99%